(untitled) (Web of Teachers: Inderscience Research, 2025)
This study explores the innovative forms of shaping Oriental education in primary grades in Uzbekistan. It examines the integration of traditional Eastern values and modern pedagogical methods, assessing their effectiveness through statistical analysis and comparative evaluation. The findings highlight the impact of technology, gamification, and collaborative learning on pupils’ engagement and retention rates. The research also identifies key challenges, such as access to technology and teacher training, and provides recommendations for further educational improvements.